A new approach to assess myocardial work by non-invasive left ventricular pressure–strain relations in hypertension and dilated cardiomyopathy. (20th September 2018) - Chan, Jonathan; Edwards, Natalie F A; Khandheria, Bijoy K; Shiino, Kenji; Sabapathy, Surendran; Anderson, Bonita; Chamberlain, Robert; Scalia, Gregory M
Abstract: Aims: Non-invasive left ventricular (LV) pressure–strain loop (PSL) provides a novel method of quantifying myocardial work (MW) with potential advantages over conventional global longitudinal strain (GLS) by incorporating measurements of myocardial deformation and LV pressure. We investigated different patterns of LV PSL and global MW index (GWI) in patients with hypertension (HTN) and dilated cardiomyopathy (CMP). Methods and results: Seventy-four patients underwent transthoracic echocardiography and strain analysis before coronary angiography. Patients were divided into three groups: control, HTN, and CMP. GWI was calculated as the area of the LV PSL as a product of strain × systolic blood pressure. MW efficiency (GWE) is derived from the percentage ratio of constructive work (GCW) to sum of constructive work (GCW) and wasted work (GWW). Influences of HTN and LV function on its relationship with MW were evaluated. GLS and LV ejection fraction were preserved in the HTN group with no difference from controls. GWI was significantly higher in moderate to severe HTN patients ( P = 0.004) as a compensatory mechanism to preserve LV contractility and function against an increase in afterload. GWE was preserved in HTN patients due to the proportional increase in GCW and GWW. GLS, GWI, and GWE were significantly reduced in CMP ( P < 0.05), with a trend in rightward shift and reduction in the LV PSL. Conclusion: GWI is a potential new technique that allows better understanding of the relationship between LV remodelling and increased wall stress under different loading conditions.